THE STUDY OF ASTRONOMY LINKED TO THE "ENGLISH FOR SPECIFIC PURPOSES" APPROACH: ADVANTAGEOUS POSSIBILITIES IN HIGH SCHOOL - Rodrigues, Janete; Cananosque Neto, Henrique (Didactic Astronomy Observatory Newsletter, 2026)
The Teaching of Astronomy has gained increasing importance in the Brazilian educational landscape, particularly due to its role in promoting scientific literacy and stimulating students' interest in nature and the exact sciences. Its interdisciplinary nature allows connections between various fields of knowledge, such as Physics, Mathematics, Geography, and History, and fosters the critical and inquisitive development of students. At the same time, the teaching of foreign languages, particularly English, has adopted practices sensitive to the specific demands of different areas of knowledge, such as English for Specific Purposes (ESP). The general objective of this research is to analyze the potential and advantages of integrating astronomy with the ESP approach in Secondary Education and to evaluate its impact on students' science and English language learning. This research is characterized as a qualitative literature review, whose purpose is to gather, analyze, and critically interpret the existing scientific production on the relation between the Teaching of Astronomy and the ESP approach in the context of Secondary Education. The integration between the Teaching of Astronomy and the ESP approach proves to be an innovative and necessary educational strategy for the contemporary Secondary Education context. Furthermore, the connection between Astronomy and ESP contributes to overcoming curricular fragmentation and building a more contextualized and humanizing education. This study reaffirms that scientific and linguistic education should not be considered as separate fields, but as complementary dimensions of the same holistic education.
Keywords: Interdisciplinary Education; Secondary Education; English for Specific Purposes (ESP); Astronomy Education